202. Quantitative evaluation and optimization of daily on-line shift in prostate cancer treatment using control charts. (December 2018) - Strolin, S.; Ungania, S.; Bruzzaniti, V.; Rao, M.; Montano, M.; Digiesi, G.; Sanguineti, G.; Strigari, L.
Abstract : Purpose: Image-guided radiotherapy (IGRT) is daily used to correct patient setup errors based on the bony anatomy and soft-tissue contrast. When setup errors are larger than expected ones, on-line imaging are repeated to verify the fulfillment of alignment criteria but number, frequency and causes of repetition cannot be investigated with the conventional information registered in the record and verify (R&V) systems. This study aims at quantitative evaluating daily on-line shift in prostate cancer patients using control charts and at investigating their potential causes in order to reduce the time needed for patients' setup thus improving the treatment. Methods: A subset of 24 prostate cancer treatments has been enrolled in this work. A homemade software was developed for pre-treatment data collection to complete the information automatically registered in the R&V system. Control charts method has been used to study the CBCT-based setup errors and to investigate how a process changes over time. Multivariate analysis was performed for the variable repetition, for the 3D error and for single direction error. Results: For all investigated patients, the reasons of repetition have been extrapolated from the software. Multivariate analysis revealed that significant prognostic variable of CBCT repetition were: the drinking time before treatment, the inclusion of pelvic nodes in the treatment, the rectum volume and length, the bladder volume. The process appeared to be not under control and requires corrective actions. Conclusion: Our software allows collecting information useful to be discussed in a clinical audit with the aim of decreasing the in-room time of patients without losing the benefit of the image-based investigation. The systematic and random setup errors calculated for each patient through the use of control charts permit to take under control the entire process and identify corrective actions.